Atomically Interfacial Engineering on Molybdenum Nitride Quantum Dots Decorated N‐doped Graphene for High‐Rate and Stable Alkaline Hydrogen Production. Issue 36 (26th October 2022) - Huang, Yichao; Zhou, Wenbo; Kong, Weichao; Chen, Lulu; Lu, Xiaolong; Cai, Hanqing; Yuan, Yongrui; Zhao, Lianming; Jiang, Yangyang; Li, Haitao; Wang, Limin; Wang, Lin; et al.
Abstract: The development of low‐cost, high‐efficiency, and stable electrocatalysts for hydrogen evolution reaction (HER) under alkaline conditions is a key challenge in water electrolysis. Here, an interfacial engineering strategy that is capable of simultaneously regulating nanoscale structure, electronic structure, and interfacial structure of Mo2 N quantum dots decorated on conductive N‐doped graphene via codoping single‐atom Al and O (denoted as AlO@Mo2 N‐NrGO) is reported. The conversion of Anderson polyoxometalates anion cluster ([AlMo6 O24 H6 ] 3−, denoted as AlMo6) to Mo2 N quantum dots not only result in the generation of more exposed active sites but also in situ codoping atomically dispersed Al and O, that can fine‐tune the electronic structure of Mo2 N. It is also identified that the surface reconstruction of AlOH hydrates in AlO@Mo2 N quantum dots plays an essential role in enhancing hydrophilicity and lowering the energy barriers for water dissociation and hydrogen desorption, resulting in a remarkable alkaline HER performance, even better than the commercial 20% Pt/C. Moreover, the strong interfacial interaction (MoN bonds) between AlO@Mo2 N and N‐doped graphene can significantly improve electron transfer efficiency and interfacial stability. As a result, outstanding stability over 300 h at a current density higher than 100 mA cm −2 is achieved, demonstrating great potential for the practical application of this catalyst. Abstract : An atomically interfacialengineering strategy is developed for simultaneous regulation of nanostructure, electronic structure and interface on single atomic aluminum and oxygenco‐doped molybdenumnitride quantum dots decorated conductive nitrogen‐dopedgraphene (AlO@Mo2 N‐NrGO), which shows a remarkable high‐rate alkaline HER performance, superior to commercial platinumcarbon (20% Pt/C), and an outstanding stability over 300 hours at 114 mA cm −2 .